Empowering Women through the Processing of Shrimp Waste into Local Wisdom–Based Entrepreneurial Products - K. Kartini; Rahmi Nur Islami; Shinta Tri Kismanti; Firdan Nurdin; J. Jumadi; Anggun Sarwana Natasya; Maya Nur Melisah (Manunggal Halim Jaya, 2026)
This Community service program addresses the pressing issue of environmental pollution caused by shrimp processing waste in the coastal area of Beach of Selumit, Tarakan City. The program aims to empower women by transforming this shrimp waste, which poses an ecological threat, into local wisdom-based entrepreneurial products. Conducted in collaboration with BKM Sejahtera as the community partner, the initiative focused on converting shrimp heads and shells into natural powdered fertilizer and shrimp broth powder. Alongside waste processing training, the program enhanced women's financial literacy through a household financial literacy handbook and promoted digital marketing via the